Governos estaduais no ambiente federativo inaugurado pela constituiç\~ao federal de 1988: Aspectos políticos e institucionais de uma atuaç\~ao constrangida - Ricardo Ismael (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper discusses the role of the state governments in the Brazilian federative system in the post-1988 Federal Constitution period, which is much characterized by cooperative and competitive mechanisms between the Union and the states and among the states themselves. The state governments lost political stature while the federal government managed to gain legitimacy in the political and electoral processes, managed to establish a stable allied political basis in the National Congress, as well as to move towards a higher level of control over the subnational public finances in the Fernando Henrique government and to broaden its powers in the formulation of public policies in the Luiz Inácio Lula da Silva government. It is not desirable to return to a scenario similar to the one in the eighties, when one could observe a governors federative system. But we also shouldn't let flourish some aspects that were present in the two prior decades, such as the permanent distrust in regards of the state expenses and a federative scenario in which one does not know where the Union powers start or finish.
Keywords: H1; H7; H77; 330; federalism; intergovernmental relations; state governments; governance capabilities